Quantifying BrO and SO2 distributions in volcanic plumes: recent advances in imaging Fabry-Pérot interferometer correlation spectroscopy - Nies, Alexander; Heimann, Jaro; Fuchs, Christopher; Kuhn, Jonas; Bobrowski, Nicole; Platt, Ulrich (Frontiers in Earth Science, 2023)
Bromine monoxide (BrO) and sulphur dioxide (SO2) are two gases frequently observed in volcanic plumes by spectroscopic techniques capable of continuous gas monitoring like, e.g., Differential Optical Absorption Spectroscopy (DOAS). The spatio-temporal resolution of DOAS measurements, however, only allows to determine average gas fluxes (minutes to hours resolution). In particular, it is insufficient to record two-dimensional images of SO2 and BrO in real-time (seconds time resolution). Thus, it is impossible to resolve details of chemical conversions of reactive plume constituents. However, these details are vital for further understanding reactive halogen chemistry in volcanic plumes. Therefore, instruments that combine high spatio-temporal resolution and high gas sensitivity and selectivity are required. In addition, these instruments must be robust and compact to be suitable for measurements in harsh and remote volcanic environments. Imaging Fabry-Pérot interferometer (FPI) correlation spectroscopy (IFPICS) is a novel technique for atmospheric trace gas imaging. It allows measuring atmospheric gas column density (CD) distributions with a high spatial and temporal resolution, while at the same time providing selectivity and sensitivity comparable to DOAS measurements. IFPICS uses the periodic transmission spectrum of an FPI, that is matched to the periodic narrowband (vibrational) absorption features of the target trace gas. Recently, IFPICS has been successfully applied to volcanic SO2. Here we demonstrate the applicability of IFPICS to much weaker (about two orders of magnitude) trace gas optical densities, such as that of BrO in volcanic plumes. Due to its high reactivity, BrO is extremely difficult to handle in the laboratory. Thus, based on the similarity of the UV absorption cross sections, we used formaldehyde (HCHO) as a spectral proxy for BrO in instrument characterization measurements. Furthermore, we present recent advances in SO2 IFPICS measurements and simultaneous measurements of SO2 and BrO from a field campaign at Mt Etna in July 2021. We find photon shot-noise limited detection limits of 4.7 × 1017 molec s0.5 cm−2 for SO2 and of 8.9 × 1014 molec s0.5 cm−2 for BrO at a spatial resolution of 512 × 512 pixels and 200 × 200 pixels, respectively. Furthermore, an estimate for the BrO to SO2 ratio (around 10-4) in the volcanic plume is given. The prototype instrument presented here provides spatially resolved measurements of the reactive volcanic plume component BrO. The temporal resolution of our approach allows studies of chemical conversions inside volcanic plumes on their intrinsic timescale.
Gesehen am 26.6.2023
Im Titel ist "2" bei "SO2" tiefgestellt